Educational Environment in the Globalization Era Perspective of Islamic Education Philosophy - Anwar, Saiful; Zukhrufin, Fina Kholij (Tahta Media Group, 2022)
The purpose of this study is to describe how the educational environment in the era of globalisation from the perspective of Islamic education philosophy, both the family, school, community and social media environment. This type of research is qualitative with a literature study design through the use of databases as an online-based journal article search engine; Databases such as Jstor, Sage, Proquest, Elsevier, Emerald Insight, Garuda and Google Scholars were used for the purposes of this research covering the period 2013 to the end of October 2023, using the keywords educational environment, globalisation era, Islamic perspective, and philosophy of education, a total of fifty articles were found. Data analysis was conducted by first collecting articles related to the topic of discussion, then limiting the number of articles according to the topic, then presenting the data, and finally making conclusions. The results of this study found that the role of the educational environment in the context of Islamic education has an increasingly deep relevance by observing the three main aspects of the educational environment, namely family, school, and society, in a global era like today, the educational environment lists new offers that are also included in the category of educational environments, namely social media. Where social media currently has a very significant influence on humans who are not limited by age, it can be a positive influence and also a negative influence, just how social media users direct themselves with experience from the three previous educational environments.